Segmental vitiligo and nevus depigmentosus. - Milano, A. (European Journal of Pediatric Dermatology, 2017)
Differential diagnosis between vitiligo and nevus depigmentosus is sometimes difficult; it is based on the history, physical examination and in subjects with little melanin on Wood’s light; exceptionally, we can resort to histology showing in vitiligo but not in nevus depimentosus absence of melanocytes. The history highlights the early onset of nevus depigmentosus, the mobility of vitiligo lesions and their reddening in the sun. However, congenital vitiligo does exist especially in the ano-genital region, and in nevus depigmentosus the mother can notice initially the more extensive and evident lesions and later the less visible. Physical examination is diriment in dark-skinned subjects and when it highlights repigmentation in vitiligo; however, the exceptional case of a reverse mutation must be considered in nevus depigmentosus. The distribution of lesions is useful only in the case of bilateral and symmetrical vitiligo.